THE CONSISTENCY OF SENIOR HIGH SCHOOL STUDENTS IN ANSWERING MATHEMATICS QUESTIONS IN THE FINAL OF SEMESTER ASSESSMENT - Nursela Afiqa; Suciati Suciati; Ika Noviantari; Arief Ertha Kusuma (Jurnal Pendidikan Matematika dan IPA)
The purpose of this study is 1) to analyse the response patterns of class XI high school students to the final Assessment, 2) to estimate the parameters of mathematics questions for the Class XI Final Assessment, and 3) to describe the consistency of class XI students' answers in the final Assessment. This research is the ex post facto type of research. Data collection techniques are carried out using documentation of high school students' responses in answering mathematics questions in the final odd semester assessment of 194 students. Student responses were analysed using the 2-PL (Logistic Parameter) model with the help of the R program. The item difficulty level was between -10.266 to 1.445, and the item differentiation index was -0.946 to 2.476. Most of the students' ability estimates were in the medium category with an interval of 1≤θ≤ 1. Based on the item parameters and students' abilities, it was found that 132 students were consistent in answering questions, and 62 students were inconsistent in answering questions, meaning that 62 students answered questions not based on their abilities. The results showed that the majority of students consistently answered the questions. This means that the scores obtained by students are in accordance with the students' abilities.